2015
DOI: 10.3109/08958378.2015.1066904
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory deposition of inhaled nanoparticles in humans

Abstract: Context Inhaled nanoparticles can migrate to the brain via the olfactory bulb, as demonstrated in experiments in several animal species. This route of exposure may be the mechanism behind the correlation between air pollution and human neurodegenerative diseases, including Alzheimer’s disease and Parkinson’s disease. Objectives This manuscript aims to (1) estimate the dose of inhaled nanoparticles that deposit in the human olfactory epithelium during nasal breathing at rest and (2) compare the olfactory dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 70 publications
(117 reference statements)
2
88
0
5
Order By: Relevance
“…One cited limitation of rodent models of inhaled air pollution has been that rodents, unlike humans, are obligate nose-breathers and thus dosing to mouse results in higher exposures relative to humans. However, this may be a minimal or negligent concern according to a recent study based on computational modeling using an anatomically accurate model of the human nasal cavity that found that the olfactory dose per unit surface area is actually estimated to be higher in humans for 1-7 nm particles based on the larger inhalation rates of humans [196]. The latter is of particular note as emphasized in a recent editorial [197], given the presence in fly ash and car exhaust of a significant fraction of particles below 10 nm, often overlooked because of measurement difficulty [198].…”
Section: Discussionmentioning
confidence: 99%
“…One cited limitation of rodent models of inhaled air pollution has been that rodents, unlike humans, are obligate nose-breathers and thus dosing to mouse results in higher exposures relative to humans. However, this may be a minimal or negligent concern according to a recent study based on computational modeling using an anatomically accurate model of the human nasal cavity that found that the olfactory dose per unit surface area is actually estimated to be higher in humans for 1-7 nm particles based on the larger inhalation rates of humans [196]. The latter is of particular note as emphasized in a recent editorial [197], given the presence in fly ash and car exhaust of a significant fraction of particles below 10 nm, often overlooked because of measurement difficulty [198].…”
Section: Discussionmentioning
confidence: 99%
“…8B from [4], supplemented by our curve. In this figure, three curves reflect the results obtained for [4][5][6], the remaining four represent calculations for different original models. In four papers [4][5][6][7], the Euler approach was used to calculate particle motion, the others [8,9] and our work used the Lagrange approach.…”
Section: Comparison Of Calculation Results With Calculated and Experimentioning
confidence: 99%
“…5 comparisons of our results with the calculated [14] and experimental [15] data are presented for the d mathematical and experimental models based on the same MRI scans, which were used in [4][5][6]. Our calculations were carried out for the model shown in Fig.…”
Section: Comparison Of Calculation Results With Calculated and Experimentioning
confidence: 99%
See 2 more Smart Citations